The elephant in the dark: A new framework for cryptocurrency taxation and exchange platform regulation in the US - Koray Çalışkan (Journal of Risk and Financial Management, 2022)
The proliferation of cryptocurrencies and the remarkable expansion of novel economic practices associated with them pose an unprecedented challenge to established norms of taxation and market regulation. Drawing on two years of fieldwork, surveys, as well as big data analysis of the most valuable 100 cryptocurrencies' white papers and the terms of service agreements of all cryptocurrency exchange platforms, this paper proposes an evidence-based framework to design a novel regulation and taxation approach to cryptocurrencies and their markets by using the US as case study. This new framework calls for approaching cryptocurrencies as data money. Drawing on the material political economy of new digital financial practices, the paper locates the universe of taxable events and invisible/vague regulation areas by approaching exchange platforms as stacked economization processes. We need to make sense of these new economic spaces in order to imagine more effective regulative instruments addressing questions of economic actor protection and efficiency. The paper concludes by proposing a new instrument of taxation (Data Money Tax) and a dynamic regulative approach to cryptocurrency exchange platforms (Stack Regulation).
Keywords: 330; cryptocurrency; markets; exchange; platform; taxation; regulation; US